Metronidazole-induced encephalopathy in a patient with pyogenic spondylitis: a case report - Mizuta, Kazutaka (BMC Musculoskelet Disord, 2018)
BACKGROUND: Metronidazole is an antimicrobial agent commonly used in the treatment of several protozoal and anaerobic infections. Neurotoxicity associated with metronidazole has been rarely reported, and the incidence of metronidazole-induced encephalopathy is unknown. Therefore, the accurate diagnosis of metronidazole-induced encephalopathy is often difficult because of the rarity of the disease. CASE PRESENTATION: An 86-year-old woman suffered from pyogenic spondylitis of the lumbar spine. Parvimonas micra, a gram-positive anaerobic bacterial species and a resident of the flora of the oral cavity, was identified in the biopsy specimens. Oral administration of metronidazole (1500 mg/day) was initiated. Forty-four days after initiating metronidazole (total intake of 66 g), she complained of tingling sensations in the upper limbs. After 4 days, she complained of additional symptoms including sensory disturbance of the tongue, dysarthria, and deglutition disorder. Characteristic brain magnetic resonance imaging findings on T2-weighted fluid-attenuated inversion recovery and diffusion-weighted imaging led to the diagnosis of metronidazole-induced encephalopathy. Metronidazole was discontinued, and her neurological symptoms improved 10 days after discontinuation. At 14 days after discontinuation of oral metronidazole, abnormal findings on diffusion-weighted imaging almost disappeared. CONCLUSIONS: With the possibility of needing to prescribe metronidazole in the orthopedic field for the treatment of various infections, orthopedic surgeons are likely to encounter cases of metronidazole-induced encephalopathy. Thus, they should be able to recognize the condition and its potential complications. With increased awareness, early diagnosis with magnetic resonance imaging and discontinuation of metronidazole may become feasible when such patients are referred. Our report presents a detailed account of such a case, which may help in the early diagnosis and treatment of patients with metronidazole-induced encephalopathy. Furthermore, we recommend that patients treated with metronidazole should undergo careful and constant surveillance after starting antibiotic therapy.